Clinico-pathological findings in natural cases of "mascadera" in goats - Micheloud, Juan Francisco; Vera, Tomas Anibal; Colque Caro, Luis Adrian; Gimeno, Eduardo Juan (2018)
“Mascadera” is a chronic emaciating neuropathy affecting goats; it produces significant economic losses in many regions and its cause is unknown. Here, the histological lesions found in 15 animals naturally affected by the disease are described. Complete necropsy was performed and tissue samples were collected for histopathological study. Severe atrophy of the masseter and buccinator muscles and tongue was observed, as well as vacuolar degeneration of neurons in the nuclei of the trigeminal, facial, and glossopharyngeal nerves. No relevant lesions were observed in other tissues. These findings and the clinical signs are consistent with those observed by other authors in animals spontaneously and experimentally intoxicated with Prosopis juliflora. The disease may be due to consumption of a similar species present in our country that is still unknown. Further research on the etiology and pathogenesis of this disease is needed to establish appropriate prevention guidelines.